Measuring Cancer Drug Sensitivity and Resistance in Cultured Cells. Issue 2 (19th June 2017) - Niepel, Mario; Hafner, Marc; Chung, Mirra; Sorger, Peter K.
Abstract: Measuring the potencies of small‐molecule drugs in cell lines is a critical aspect of preclinical pharmacology. Such experiments are also prototypical of high‐throughput experiments in multi‐well plates. The procedure is simple in principle, but many unrecognized factors can affect the results, potentially making data unreliable. The procedures for measuring drug response described here were developed by the NIH LINCS program to improve reproducibility. Key features include maximizing uniform cell growth during the assay period, accounting for the effects of cell density on response, and correcting sensitivity measures for differences in proliferation rates. Two related protocols are described: one involves an endpoint measure well‐suited to large‐scale studies and the second is a time‐dependent measurement that reveals changes in response over time. The methods can be adapted to other types of plate‐based experiments. © 2017 by John Wiley & Sons, Inc.